Perekenomian pada Masa Khulafaur Rasyidin - Mara Hamdan Tambunan; Zahra Audi Maharani; Albina Humaira Manurung; Jeane Agretta Mandalika (Journal of Islamic Economics and Finance, 2025)
This research discusses the economic policies implemented during the leadership of the Khulafaur Rashidin and their impact on the welfare and stability of the Muslim community. Through a descriptive qualitative method with a literature study approach, this research analyzes key policies such as the establishment of Baitul Mal, zakat and tax management, infrastructure development, as well as administrative reforms and wealth distribution by the caliphs. The results show that these policies played an important role in creating a fair distribution of wealth, improving people's welfare, and maintaining economic and social stability. The Islamic economic principles applied, such as social justice, transparency, prohibition of usury, and market supervision, have proven to be relevant and can be an inspiration in facing modern economic challenges.